Stages of behavior change and their correlation with alcohol, tobacco and drug use in schoolchildren aged 9 to 17 in Bogotá D.C., Colombia (2019)
Introduction: Psychoactive substance use is a problem that affects schoolchildren from an early age. Objective: To describe the stages of behavior change and their correlation with alcohol, tobacco and drug use in schoolchildren of Bogotá D.C., Colombia. Materials and methods: Cross-sectional study in 6 965 schoolchildren from Bogotá D.C. Behavior change was evaluated by self-report using a structured questionnaire based on the precontemplation, contemplation, preparation and action/maintenance stages of the Transtheoretical Model. Results: 58.4% of the participants were women with a mean age of 12.7±2.3 years. Regarding illicit drug use, 6% of schoolchildren were in the precontemplation stage, 44% in contemplation, 30% in preparation and 20% in action/maintenance. With respect to alcohol consumption, 5% were in precontemplation stage, 36% in contemplation, 12% in preparation and 46% in action/maintenance. Smoking showed prevalence of 4% for precontemplation, 33% for contemplation, 12% for preparation and 51% for action/maintenance. Conclusions: The use of psychoactive substances is an increasing issue among schoolchildren. Most interviewees were in the maintenance stage of tobacco and alcohol use, and in the contemplation stage of drug use. Government efforts are required to promote preventive programs in schools. © 2019, Universidad Nacional de Colombia. All rights reserved.